2019
DOI: 10.29252/jrdms.4.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Compressive Strength of Two Resin-Reinforced Glass Ionomers: An In-Vitro Study

Abstract: Background and Aim:Although the physical properties of modern glass ionomers have been extensively reported, few studies have examined how these parameters change with age. This experimental study aimed to investigate the effect of aging on the compressive strength of resin-reinforced glass ionomers. Materials and Methods: Two glass ionomers (Fuji IX GP Fast, GC, Japan, and Ketac Universal, 3M, USA) and one composite resin (control; Filtek P60, 3M, USA) were chosen for this study. Both glass ionomers were enca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…This may be due to the presence of larger glass particles and larger voids seen in GC Fuji IX GP Fast GIC. 22 This result was in accordance with the studies conducted by Seirawan et al 17 and Arjomand et al, 23 which show the least compressive strength of GC Fuji IX GP fast GIC.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to the presence of larger glass particles and larger voids seen in GC Fuji IX GP Fast GIC. 22 This result was in accordance with the studies conducted by Seirawan et al 17 and Arjomand et al, 23 which show the least compressive strength of GC Fuji IX GP fast GIC.…”
Section: Discussionsupporting
confidence: 90%
“…9 GIC has low physical properties in comparison with other restoration material such as composite resin and is continuously researched to improve its properties by modifying its components. 10,11 The study from Arjomand et al showed that the compressive strength of various GIC increases with aging; however, these GICs fail to perform as efficient as composite resin. 11 Bao et al on their research used GIC-modified material through the addition of CMC powder in a certain amount of mass (0.00625wt.%, 0.0125wt.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The study from Arjomand et al showed that the compressive strength of various GIC increases with aging; however, these GICs fail to perform as efficient as composite resin. 11 Bao et al on their research used GIC-modified material through the addition of CMC powder in a certain amount of mass (0.00625wt.%, 0.0125wt. %, 0.025wt.%, and 0.0375wt.)…”
Section: Introductionmentioning
confidence: 99%